A Rectourethral Fistula due to Transrectal High-Intensity Focused Ultrasound Treatment: Diagnosis and Management. (9th December 2012) - Fiaschetti, Valeria; Manenti, Guglielmo; Di Poce, Isabelle; Fornari, Maria; Ricci, Aurora; Finazzi Agrò, Enrico; Simonetti, Giovanni
Abstract : Colovesical fistula (CVF) is an abnormal connection between the enteric and the urinary systems. The rectourethral fistula (RUF) is a possible but extremely rare complication of treatment of prostate cancer with "transrectal High-Intensity Focused Ultrasound (HIFU) treatment." We present a case of CVF due to HIFU treatment of recurrent prostate cancer. The case was assessed with cystography completed with a pelvic CT scan—with MPR, MIP, and VR reconstruction—before emptying the bladder. Since the CT scan confirmed that the fistula involved solely the urethra and excluded even a minimal involvement of the bladder, it was possible to employ a conservative treatment by positioning a Foley catheter of monthly duration, in order to allow the urethra to rest. Still today, after 6 months, the patient is in a good clinical condition and has not shown yet signs of a recurrence of the fistula.